Research progress on the association of autophagy with invasion and metastasis of malignant melanoma - Xiang GAO; Xuening ZHAO; Zhao HAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Autophagy is a unique biological phenomenon of eukaryotic cells. Autophagy plays a very important role in promoting the survival of cells and actively adapting to different environments. Autophagy plays a double-edged role in the development of tumor and metastasis. The research results on the link between autophagy and melanoma are inconsistent, likely due to the intrinsic heterogeneity of melanoma and the difference in methodology of detecting autophagy. However, the results of studies on different aspects support a link between autophagy and malignant melanoma, especially the important role of autophagy in targeted drug therapy. This paper reviews the dual role of autophagy in the biological processes of melanoma invasion and metastasis, in order to provide clues for the development of new therapeutic regimens and biomarkers for malignant melanoma.